Niche differences may explain the geographic distribution of cytotypes in Erysimum mediohispanicum - Muñoz-Pajares, A J; Perfectti, F; Loureiro, J; Abdelaziz, M; Biella, P; Castro, M; Castro, S; Gómez, J M (Plant biology (Stuttgart, Germany), 2018)
Polyploidisation has played an important role in plant diversification, and variation in ploidy level may be found not only between species of the same genus, but also within a single species. Although establishing the adaptive significance of polyploidy to explain the geographic distribution of cytotypes is challenging, the occurrence of different cytotypes in different ecological niches may suggest an adaptive role of genome duplication. We studied the adaptive significance of the geographic distribution of cytotypes across the entire distribution range of the endemic Erysimum mediohispanicum (Brassicaceae). For that, we have used climate variables, population elevation and soil properties to model ecological niches for the different cytotypes. In addition, we analysed the effect that ploidy level has on the floral phenotype. We found a clear geographic pattern in the distribution of cytotypes, with diploid individuals occurring in the southernmost part of the distribution range, while tetraploids were found in the northern area. A contact (mosaic) zone between both cytotypes was identified, but diploids and tetraploids occur in sympatry in only one population (although in a highly unbalanced proportion). Gene flow between different cytotypes seems to be negligible, as evident from an almost complete absence of triploids and other minority cytotypes. Niches occupied by both cytotypes showed subtle, but significant differences, even in the contact zone. Precipitation was higher in regions occupied by tetraploid individuals, which present wider corolla tubes and thinner but taller stalks than diploids. Our findings highlight the potential role of polyploidy in the ecological adaptation of E. mediohispanicum to both abiotic factors and biotic interactions.
Keywords: nadmořská výška; polyploid aggregate; zeměpis; Ecosystem; Climate variables; tok genů; podnebí; phenotypic traits; Climate; biologická evoluce; Geography; Soil; Biological Evolution; Altitude; Erysimum; contact zone; tetraploidie; ekosystém; Polyploidy; ecological adaptation; Tetraploidy; půda; polyploidie; Gene Flow